Digitalization of toxicology: improving preclinical to clinical translation - Berridge, Brian R.; Baran, Szczepan W.; Kumar, Vivek; Bratcher-Petersen, Natalie; Ellis, Michael; Liu, Chang-Ning; Robertson, Timothy L. (Frontiers in Toxicology, 2024)
Though the portfolio of medicines that are extending and improving the lives of patients continues to grow, drug discovery and development remains a challenging business on its best day. Safety liabilities are a significant contributor to development attrition where the costliest liabilities to both drug developers and patients emerge in late development or post-marketing.Animal studies are an important and influential contributor to the current drug discovery and development paradigm intending to provide evidence that a novel drug candidate can be used safely and effectively in human volunteers and patients. However, translational gapssuch as toxicity in patients not predicted by animal studies -have prompted efforts to improve their effectiveness, especially in safety assessment.More holistic monitoring and 'digitalization' of animal studies has the potential to enrich study outcomes leading to datasets that are more computationally accessible, translationally relevant, replicable, and technically efficient. Continuous monitoring of animal behavior and physiology enables longitudinal assessment of drug effects, detection of effects during the animal's sleep and wake cycles and the opportunity to detect health or welfare events earlier.Automated measures can also mitigate human biases and reduce subjectivity.Reinventing a conservative, standardized, and traditional paradigm like drug safety assessment requires the collaboration and contributions of a broad and multi-disciplinary stakeholder group. In this perspective, we review the current state of the field and discuss opportunities to improve current approaches by more fully leveraging the power of sensor technologies, artificial intelligence (AI), and animal behavior in a home cage environment.